16. (01.07)
An equation is shown below:
4(x - 3) - 5(x + 1) = 3
Which statement shows a correct next step in solving the equation? (1 point)
The equation can become 4x - 3 - 5x + 1 = 3 by applying the associative property of multiplication.
The equation can become 4x - 3 - 5x + 1 = 3 by applying the distributive property.
The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property.
The equation can become 4x - 12 - 5x - 5 = 3 by applying the associative property of multiplication.
17.(01.07)
00:07:38